Pembelajaran Daring Dengan Google Meet Untuk Meningkatkan Keaktifan Mahasiswa PGSD - Firman, Sulfiana; Suardi, Renaldi; Nur, Andi Muafiah; N, Nasrun (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This research is a qualitative research. The aim of this research is to describe the concept of online lectures via Google Meet to increase student activity. The subjects of this research were 1st semester PGSD students in online lectures for the Basic Elementary Science Concepts course, consisting of 21 people in class F and 24 people in class G. This research was conducted in the odd semester of the 2023/2024 academic year. This research was conducted in 8 meetings. Each meeting requires 1 hour 30 minutes of learning time. Each class is divided into 10 groups consisting of between 2-3 students. The data collection technique in this research is through documentation (group presentations, student online attendance) and questionnaires. The data in this research will be analyzed by using a qualitative descriptive method. The result of this research showed that online learning using Google Meet can increase student activity in the learning process. This can be proven from the enthusiasm of students during group discussions as well as the presence of students in attending lectures and student responses through the distribution of questionnaires.